2010
DOI: 10.3109/10799893.2010.487493
|View full text |Cite
|
Sign up to set email alerts
|

The estrogen-related receptor alpha: the oldest, yet an energetic orphan with robust biological functions

Abstract: The estrogen-related receptor alpha (ERRalpha) is an orphan nuclear receptor (ONR) that by binding to DNA sites controls gene expression in association with coactivators and corepressors. ERRalpha was the first ONR to be identified; however, its natural endogenous ligand(s) is still unknown. ERRalpha by acting as a transcription factor has been shown to regulate a large array of genes, thereby controlling numerous metabolic pathways and other biological functions in animals. Of late, the expression of ERRalpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 57 publications
3
30
0
2
Order By: Relevance
“…Besides its impact on the synthesis of nucleic acids within HCMV-infected cells by supporting the accumulation of nucleoside and deoxynucleoside mono-, di-, and triphosphates, ERRα is generally required for cells and tissues with high energy demand (55), and it is likely to impact viral replication and spread through additional effects on metabolism. ERRα promotes a Warburg-like effect by inducing a metabolic shift from oxidative phosphorylation to glycolysis (27), and it has also been shown to maintain the TCA cycle by inducing anaplerotic replenishment of TCA cycle metabolites (27).…”
Section: Discussionmentioning
confidence: 99%
“…Besides its impact on the synthesis of nucleic acids within HCMV-infected cells by supporting the accumulation of nucleoside and deoxynucleoside mono-, di-, and triphosphates, ERRα is generally required for cells and tissues with high energy demand (55), and it is likely to impact viral replication and spread through additional effects on metabolism. ERRα promotes a Warburg-like effect by inducing a metabolic shift from oxidative phosphorylation to glycolysis (27), and it has also been shown to maintain the TCA cycle by inducing anaplerotic replenishment of TCA cycle metabolites (27).…”
Section: Discussionmentioning
confidence: 99%
“…These orphan receptors have homology to estrogen receptors and are thought to have constitutive transcriptional activity that is regulated by cofactor interactions with transcription factors such as PGC1 α / β (peroxisome proliferator-activated receptor gamma coactivator 1) and deacetylation by Sirt1 (sirtuin 1) (41). Expression of ERR β is not well characterized in the immune system, but ERR α is ubiquitously expressed in lymphocytes and macrophages.…”
Section: Transcriptional Regulators Of Metabolismmentioning
confidence: 99%
“…Estrogen-related receptor α (ERRα) belongs to a nuclear receptor superfamily characterized by their high levels of sequence identity to estrogen receptors, and the primary role of ERRα is in energy metabolism (9). A study has demonstrated that activation of the peroxisome proliferator-activated receptor g coactivator 1-α (PGC-1α)/ERRα pathway increases VEGF expression and angiogenesis in endothelial cells, which suggests that ERRα may be involved in the pathogenesis of DR (10).…”
Section: Introductionmentioning
confidence: 99%